Supervision of Medicinal Products by BPOM Consumer Protection Legal Perspective (ED/DEG Tainted Syrup Drug Case) - Rabbany, Muhammad Burhanuddin (Universitas Syiah Kuala, 2023)
The case of tainted syrup with diethyllenglikol (ED/DEG) in Indonesia has raised serious concerns regarding the supervision of medicinal products by the Food and Drug Supervisory Agency (BPOM). This article presents a legal analysis of consumer protection of this case, as well as highlights the role of BPOM in carrying out the task of supervising medicinal products. The case of ED/DEG tainted syrup became the public spotlight when a number of consumers experienced negative health impacts after consuming the product. This incident raises questions about the effectiveness of BPOM supervision in protecting consumers from unsafe drug products. This article attempts to outline the legal aspects involved in this case, including consumer protection laws, drug regulation, and BPOM's authority. The results of this analysis provide an overview of the complexity of legal issues that arise in the case of ED/DEG tainted syrup drugs, and emphasize the importance of strengthening the drug product supervision system in Indonesia to better protect consumers. The implementation of drug supervision by BPOM in the implementation system is quite good, but the implementation has not been optimal. There are regulatory loopholes that have been realized by BPOM that should be able to make additional arrangements.